Implementation of Sequential Pattern Discovery using Equivalent classes (SPADE) on MONSAKUN Media for Exploring and Digging for Information on German Language Learning - Herri Akhmad Bukhori; Sunarti Sunarti; Tiksno Widyatmoko; Djoko Saryono; Hari Putranto; Irawan Dwi Wahyono6 (Indonesian Journal of Learning Education and Counseling, 2023)
The use of technology is often used to support the learning process, one of which is the German Learning language learning media. The use of learning media in the actions of the student learning process that has been carried out can store data in the form of a log database. A database log is a sequence of student learning processes that have been generated that need to be processed and analyzed to identify the same learning patterns to help lecturers provide appropriate input. This study aims to utilize a log database of German Learning learning media using the sequential pattern method to explore useful information from the student's learning process when working on German Learning language problems. The algorithm used is Sequential Pattern Discovery using the Equivalent class (SPADE). Furthermore, this study uses an algorithm to identify the same learning patterns based on student learning activities when using MONSAKUN learning media. Moreover, the learning pattern that has been successfully obtained will be carried out by extracting information to analyze the same learning pattern based on the category of the student's ability to solve problems. Based on the results of the implementation and analysis that has been carried out on 20 German Learning language questions that have been successfully processed in the MONSAKUN learning media, six patterns of learning activities that vary on each question and level are produced, namely: pattern 1, pattern 2, pattern 3, pattern 4, pattern 5, and pattern 6. Each pattern requires further feedback and responses to optimize students' learning progress in Learning German Learning